Design of Internship Information Systems Using Prototyping Method in PT. Gramedia Asri Media - Fransiska Wahyuning Kurniawati; Christ Rudianto; Augie David Manuputty; Agustinus Fritz Wijaya (Journal of Information System and Informatics, 2020)
Human Resources (HR) is one of the important things that determines the success of the services of a company, one of the things done to prepare a good HR is to launch a program of Job Training (PKL) or also known as an internship. PT.Gramedia Asri Media became one of the companies implementing the internship program, but the existing internship program was still carried out manually by distributing information to tertiary institutions via email. This journal aims to create an apprenticeship information system design by developing a system using the prototyping method so that the apprenticeship process can be carried out in a single system from the dissemination of information to the resolution of administrative problems related to finance and the need for an apprenticeship approval document. The system development method used therein is the prototyping method that starts from analyzing user needs to creating a User Interface (UI) that is easily understood by the user. The apprenticeship information system is expected to make the apprenticeship process more effective both in registering and processing the internship data contained therein.